Penggunaan Metode Variatif dengan Pendekatan Saintifik dalam Pembelajaran Fikih di Madrasah Ibtidaiyah Kota Lhokseumawe - Maawiyah, Aisyah; Fauziana, Fauziana (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2023)
This research was conducted at Madrasah Ibtidaiyah Kota Lhokseumawe to explore the use of varied methods with a scientific approach in teaching Fiqh, as well as the constraints and efforts made by teachers in implementing them. This study used a qualitative approach with data collection techniques through interviews and observations. The research respondents consisted of Fiqh teachers and the Head of Madrasah Ibtidaiyah Kota Lhokseumawe. The results of the study found that teachers at Madrasah Ibtidaiyah Kota Lhokseumawe used varied methods in teaching Fiqh, such as lectures, question and answer sessions, discussions, and demonstrations. They also applied a scientific approach with steps including observation, questioning, exploration, association, and communication. However, there were constraints such as a lack of reading materials and teaching media, a lack of understanding of the scientific approach, and a lack of support in facilities and infrastructure. To improve the effectiveness of teaching, it is recommended that teachers be more creative in creating teaching media, searching for teaching materials, and opening up discussion spaces with students. School principals also need to provide support and participate in training to enhance teachers' understanding of curriculum implementation.